Accounting for Lebanese Muslims' perspectives on the Islamic state (ISIS): religious militancy, sectarianism and personal attributions. Issue 3 (3rd July 2017) - Haddad, Simon
ABSTRACT: This article seeks to determine the correlates of Lebanese Muslims perceptions of the Islamic State (ISIS) which are measured using the hypotheses that commitment to political Islam, young age, education and occupational status would predict approval of ISIS. In view of the accentuated polarisation between Sunnis and Shiis along sectarian lines, it is proposed that dislike for the Shiis would enhance the level of support for ISIS. The study was based on a cross-sectional survey Lebanese Muslims ( N = 302) administered during the fall of 2015.The suggestion is that adherence to the tenets of political Islam, sectarianism and educational attainment are major predictors of endorsement for ISIS.